Near-infrared spectroscopy combined with intravascular ultrasound in carotid arteries - Štěchovský, Cyril; Hájek, Petr; Horváth, Martin; Špaček, Miloslav; Veselka, Josef (The international journal of cardiovascular imaging, 2016)
Limited insights into the pathophysiology of the atherosclerotic carotid stenosis are available in vivo. We conducted a prospective study to assess safety and feasibility of intravascular ultrasound (IVUS) combined with near-infrared spectroscopy (NIRS) in carotid arteries. In addition, we described the size and the distribution of lipid rich plaques in significant atherosclerotic carotid stenoses. In a prospective single centre study 45 consecutive patients (mean age 66 ± 8 years) with symptomatic (≥50 %) or asymptomatic (≥70 %) stenosis of internal carotid artery (ICA) amendable to carotid stenting were enrolled. A 40 mm long NIRS-IVUS pullback through the stenosis was performed. IVUS and NIRS data were analyzed to assess minimal luminal area (MLA), plaque burden (PB), remodeling index (RI), calcifications, lipid core burden index (LCBI), maximal LCBI in any 4 mm segment of the artery (LCBImx) and LCBI in the 4 mm segment at the site of minimal luminal area (LCBImxMLA). NIRS-IVUS pullbacks were safely performed without overt clinical events. LCBImx was significantly higher than LCBImxMLA (369.1 ± 221.1 vs. 215.7 ± 2589; p = 0.004). Conversely, PB was significantly larger at the site of MLA (87.4 ± 4.8 % vs. 58.3 ± 18.2 %; p < 0001). Distance of the NIRS-IVUS frame with the highest LCBI from the site of MLA was 6.5 ± 7.7 mm. Eighty percent of frames with maximal LCBI were localized within 10 mm from the site of MLA and 67 % proximally to or at the site of MLA. This study suggested safety and feasibility of the NIRS-IVUS imaging of the carotid stenosis and provided insights on the distribution of lipids in the carotid stenosis. Lipid rich plaques were more often located in the sites with a milder stenosis and smaller plaque burden than at the site of MLA.
Keywords: senioři; Carotid atherosclerotic disease; Carotid Artery, Internal; lipidy; stupeň závažnosti nemoci; Stroke; Predictive Value of Tests; intervenční ultrasonografie; Middle Aged; mužské pohlaví; prediktivní hodnota testů; Prospective Studies; studie proveditelnosti; Lipid rich plaque; cévní mozková příhoda; Near-infrared spectroscopy; Intravascular ultrasound; Lipids; aterosklerotický plát; Ischemic Attack, Transient; ženské pohlaví; blízká infračervená spektroskopie; prospektivní studie; Asymptomatic Diseases; Humans; Spectroscopy, Near-Infrared; Plaque, Atherosclerotic; stenóza arteria carotis; biologické markery; Ultrasonography, Interventional; lidé středního věku; Carotid artery stenosis; Biomarkers; tranzitorní ischemická ataka; Carotid Stenosis; Female; Aged; asymptomatické nemoci; Severity of Illness Index; arteria carotis interna; Feasibility Studies; lidé; Male